Transformation of Digital Archives Management: Case Study of Dynamic Archives Information System Implementation at SMA Negeri 2 Sidoarjo - Mursyidah, Lailul; Sukmono, Rita; Masithah, Laila (Indonesian Journal Publisher, 2024)
This article discusses the transformation of archiving management from manual to digital systems at SMA Negeri 2 Sidoarjo. This study aims to analyze the implementation of the Dynamic Archiving Information System (SIKD) in improving the efficiency and effectiveness of archive management. The research method used is a case study with a qualitative approach through interviews, observations, and document analysis. The results of the study indicate that the implementation of SIKD has a positive impact on archive management, including increasing accessibility, security, and time efficiency. However, there are several challenges such as the lack of trained human resources and adequate infrastructure. In conclusion, digital transformation in archiving management is very important to support smooth administration and decision making in the educational environment.